CCAFS Knowledge by the Numbers 2019 - Ramírez, Margarita M.; Tobon, Hector; Traoré, Fatime; Samuel, Seble (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
2020 has been a challenging year; however, thanks to your efforts in reporting your outputs in MARLO, we are pleased to share with you the stats and analysis of CCAFS knowledge and data sharing achievements in 2019.